2004
DOI: 10.1373/clinchem.2004.037358
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a Candidate Reference Measurement Procedure for Serum Free Testosterone Based on Ultrafiltration and Isotope Dilution–Gas Chromatography–Mass Spectrometry

Abstract: Background:To assess the analytical validity of free testosterone (FTe) measurements, a reference measurement procedure (RMP) is required. For steroids, isotope dilution-mass spectrometry is accepted as state-of-theart technology. Because FTe is defined as the hormone fraction in serum water in equilibrium with the proteinbound fraction, the RMP should include a physical separation step. The use of equilibrium dialysis (ED) or ultrafiltration (UF) is advocated. Our objective was to develop such a candidate RMP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0
4

Year Published

2005
2005
2013
2013

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(25 citation statements)
references
References 35 publications
0
21
0
4
Order By: Relevance
“…Alternatively, methods of directly assessing the quantity of free T in serum, such as equilibrium dialysis, are more accurate, correlating well with mass spectrometry (114). However, this method is not widely available given its relative technical complexity and high economic cost.…”
Section: Hyperandrogenemiamentioning
confidence: 99%
“…Alternatively, methods of directly assessing the quantity of free T in serum, such as equilibrium dialysis, are more accurate, correlating well with mass spectrometry (114). However, this method is not widely available given its relative technical complexity and high economic cost.…”
Section: Hyperandrogenemiamentioning
confidence: 99%
“…The free fraction of steroids can be measured with dialysis or ultrafiltration of the samples (Sinha-Hikim et al, 1998;Van Uytfanghe et al, 2004), followed by instrumental analysis; alternatively it could be calculated using methods based on the dissociation constants and the law of mass action (Vermeulen et al, 1999;Ly & Handelsman, 2005).…”
Section: Lc-ms/ms In Clinical Diagnosticsmentioning
confidence: 99%
“…Details of the ID-GC-MS RMP are described elsewhere (17,(19)(20)(21)(22) (for a summary see Table 1). Calibration was done with testosterone/ [3,[4][5][6][7][8][9][10][11][12][13] C 2 ] testosterone mixtures at a 1:1 isotope ratio (Ϯ15%) prepared from 3 independent working solutions, demonstrated beforehand to not differ by Ͼ1% from each (n ϭ 6, probability 95%) (20 ).…”
Section: Id-ms Measurement Proceduresmentioning
confidence: 99%
“…sample clean-up (as used in the reference ID-GC-MS measurement procedure) and assessment of interference from other steroid hormones as part of the method validation (22 ). Our study showed that the ID-LC-MS/MS procedures for measurement of testosterone in serum have sufficient analytical sensitivity to distinguish between normogonadal, hypogonadal, and female testosterone concentrations, proper specificity, even in the low concentration range, and fairly good accuracy within the biologically derived total error limit.…”
Section: Serum Testosterone Measurement By Msmentioning
confidence: 99%